Eficácia do glyphosate e 2,4-d no controle de espécies de trapoerabas (Commelina spp.) - da Costa, Neumarcio Vilanova; Martins, Dagoberto [UNESP]; da Costa, Andreia Cristina Peres Rodrigues; Cardoso, Leonildo Alves (My University, 2011)
The aim of this study was to evaluate the efficacy of glyphosate and 2,4-D for the Commelina benghalensis, Commelina diffusa and Commelina erecta. Three experiments were conducted in a greenhouse in a completely randomized in factorial scheme 3x7+1 (three herbicides x seven periods - hour after application) for two methods for measuring absorption of herbicides (simulated rain and cut the leaves applied), and a control without application, with four replications. The herbicides used were: glyphosate (1,080 g ha -1), 2,4-D amine (720 g ha -1) and, mixture glyphosate + 2,4-D (720 + 720 g ha -1). It was evaluated seven time intervals for washing (simulating rainfall after application) and cut (simulation abortion as a strategy of defense) the leaves applied: 0, 2, 4, 6, 8, 12 and 24 hours after herbicide application (HHA). The minimum period for absorption of glyphosate alone and in mixture with 2,4-D presented a satisfactory control (> 90.0%) was around 12 HHA to C. benghalensis, C. diffusa and C. erecta, independently of washing or cut the leaves applied. This observed behavior can influence the time required without rain after herbicide application, besides that, the plants aborted part of the stem with injuries to avoid the herbicide translocation, especially when was used the 2,4-D alone. Concluded that glyphosate alone and in mixture with 2,4-D were efficient and that the differences in the control of species may be due to variation of time to absorb the herbicide.
Efficacy of glyphosate and 2,4-d in the control of diferent kinds of trapoeraba (Commelina spp.)
Keywords: Commelina benghalensis L.; Commelina diffusa Burm. f.; Commelina erecta L.; Herbicide; Tolerance